BIOLOGIA REPRODUTIVA DE COTESIA FLAVIPES (CAM.). II. EFEITO DE MÚLTIPLAS CÓPULAS SOBRE O NÚMERO DE POSTURAS, RAZÃO SEXUAL E LARVAS QUE EMERGEM DO HOSPEDEIRO DIATRAEA SACCHARALIS (F.) - Campos-farinha, A.e. De C.; Chaud-netto, J. [UNESP] (Instituto Biológico, 2025)
Cotesia flavipes (Cam.) females that have mated with one and two males were individually set aside with fifth instar Diatraea saccharalis (F.) larvae. Number of layings as well as nonviable the number of emerged parasitoids, and larvae were registered. The sex ratio was also analyzed. It was observed that parasitoid females are mostly monogamic and prefer to lay a batch of eggs once. The number of laid eggs, the offspring sex ratio and the number of nonviable larvae produced by parasitoids that mated with one and two males were similar, even when variable number of layings occurred. Results suggest that a second mating does not influence parasitoid fitness.

Fêmeas de Cotesia flavipes (Cam.) que copularam com um e dois machos foram colocadas, individual..: mente, em placas de Petri na presença de lagartas de 5º ínstar de Diatraea saccharalis (F.). O número de posturas realizadas, bem como o número de parasitóides emergidos e larvas inviáveis foram registrados. A razão sexual da prole também foi verificada. Foi observado que as fêmeas são basicamente monogâmicas e que preferem ovipositar apenas uma vez na lagarta hospedeira. O número de ovos depositados, a razão sexual da prole e o número de larvas inviáveis produzido pelas vespas que copularam com um e dois machos foi semelhante, mesmo quando elas fizeram posturas em número variável. Estes resultados sugerem que uma segunda cópula não influencia o valor adaptativo da prole deste parasitóide.
REPRODUCTIVE BIOLOGY OF COTESIA FLAVIPES (CAM). II. EFFECT OF MULTIPLE MATINGS ON THE NUMBER OF LAYINGS, OFFSPRING AND SEX RATIO OF PARASITOIDS THAT EMERGE FROM DIATREA SACCHARALIS (F.)
Keywords: Insect parasitoids; Braconidae; multiple mating; sugar-cane borer; viability; Insetos parasitóides; Braconidae; múltiplas cópulas; broca da cana-de-açúcar; viabilidade